Analisis Faktor – Faktor yang Mempengaruhi CSRD pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2017 – 2019 - Febrilian, Tiffany Nabila; Jaeni, Jaeni (Universitas Pendidikan Ganesha, 2021)
The purpose of this study was to determine the effect of the audit committee, profitability, firm size, and leverage on the corporate social responsibility disclosure (CSRD). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period 2017 – 2019 which disclose annual reports and CSR reports and the sample is determined by purposive sampling. the number of samples used in this study were 80 companies. The data that has been obtained is then processed using multiple linear regression analysis techniques with the SPSS 26 program. The results of this study indicate that the Audit Committee and Leverage have a positive and insignificant effect on CSRD, while Profitability and Company Size have a positive and significant effect on CSRD.